Understanding employee cynicism toward change in healthcare contexts. (10th May 2010) - Albrecht, Simon
As the healthcare sector continues to go through transformational change, it is important to identify organisational factors that impact on employee attitudes to change. There is limited empirical evidence about the determinants of cynicism toward change, particularly in the healthcare sector environment. In this paper, a model is proposed which identifies three key antecedents of cynicism toward change: change information, involvement with change and trust in senior management. Data were collected from two healthcare sector organisations to test the proposed model. The results of confirmatory factor analysis (CFA) and structural equations modelling (SEM) suggest that change information, involvement in change processes and trust in senior management influence cynicism toward change. More specifically, evidence is presented which suggests that involvement in change and trust in senior management directly influence cynicism toward change, and that information about change and involvement in change directly influence trust in senior management. Collectively, the antecedent variables accounted for just over 50% of the variance in cynicism toward change. In general terms, the findings will prove helpful to human resource practitioners interested in diagnosing and managing attitudes to change of healthcare employees.